Five-year clinical outcomes in patients with diabetes mellitus treated with polymer-free sirolimus- and probucol-eluting stents versus second-generation zotarolimus-eluting stents: a subgroup analysis of a randomized controlled trial. Issue 1 (December 2016) - Harada, Yukinori; Colleran, Roisin; Kufner, Sebastian; Giacoppo, Daniele; Rheude, Tobias; Michel, Jonathan; Cassese, Salvatore; Ibrahim, Tareq; Laugwitz, Karl-Ludwig; Kastrati, Adnan; Byrne, Robert
Abstract Background Improved outcomes in patients with diabetes mellitus undergoing percutaneous coronary intervention remain an unmet clinical need. We assessed the long-term efficacy and safety of novel polymer-free sirolimus- and probucol-eluting stent in diabetic patients enrolled in intracoronary stenting and angiographic results: test efficacy of sirolimus- and probucol-eluting versus zotarolimus-eluting stents 5 trial. Methods In a pre-specified subgroup analysis, outcomes of diabetic patients treated with a sirolimus- and probucol-eluting stent or a second-generation zotarolimus-eluting stent were compared. The primary endpoint was a device-oriented composite outcome comprising cardiac death, target vessel-related myocardial infarction (MI), or target lesion revascularization (TLR) at 5-year follow-up. Event-free survival was assessed using the Kaplan–Meier method. Hazard ratios (HR) and 95 % confidence intervals (CI) were estimated from univariate Cox proportional hazards models. Results A total of 870 patients with diabetes mellitus were treated with either a sirolimus- and probucol-eluting stent (n = 575) or a second-generation zotarolimus-eluting stent (n = 295). At 5 years, the rate of device-oriented composite endpoint was comparable between the sirolimus- and probucol-eluting stent and the second-generation zotarolimus-eluting stent (32.9 versus 33.4 %, HR 0.88, 95 % CI 0.76–1.26). No significant differences were observed between the sirolimus- and probucol-eluting stent and the second-generation zotarolimus-eluting stent groups in the incidence of cardiac death (15.6 versus 16.7 % HR 0.92, 95 % CI 0.63–1.32), target-vessel MI (4.6 versus 6.6 %, HR 0.73, 95 % CI 0.40–1.34), and TLR (18.6 versus 18.8 %, HR 1.00, 95 % CI, 0.72–1.41). The rate of definite or probable stent thrombosis was low and similar in both groups (2.5 versus 2.6 %, HR 1.02, 95 % CI, 0.41–2.52). Conclusions In patients with diabetes the long-term efficacy and safety of a polymer-free sirolimus- and probucol-eluting stent were comparable to a second-generation durable polymer zotarolimus-eluting stent. Trial registration ClinicalTrials.gov NCT00598533. Registered 10 January 2008